State Law, Integral Economic Justice, and Better Regulatory Practices: Promoting Economic Efficiency in Indonesia - Sugianto, Fajar; Lago, Yuber; Luna, Laurenzia (Universitas Pelita Harapan, 2023)
Indonesia as a state based on the rule of law like any other developing countries, its society is based on patterns and economic classes, overall obedience to the law is not easy. In heterogeneous society formed of groups based on religion, race, language, and wealth, it is one of the most difficult unifying factors in terms of compliance with the law. Law deals with complex social, and conflicting societies apply law as a powerful instrument of regulation and control. Although law acts as an independent agent to facilitate their complexity, with economic approach, efficiency is an ideal model that guides legal practice. It is because most people as homo economicus (except children and the profoundly retarded) in all of their activities has one thing in common, that is the need for efficiency, perhaps efficiency is the nearest we are likely to approach to a universal secular “religion”. Efficiency in law simplifies how law works in different society, especially in heterogeneous communities. This approach does not reduce law to economics (or vice versa, for that matter), it claims simply that law and economics have a lot to learn from one another. The primacy of efficiency helps to harmonize the practice of law with social practices. When such law exists, it does function as a social tool aiming at the promotion of economic efficiency that goes well with other social practices.